2014
DOI: 10.1155/2014/817613
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Extracellular Hyaluronan by Hyaluronan Synthase 3 Promotes Tumor Growth and Modulates the Pancreatic Cancer Microenvironment

Abstract: Extensive accumulation of the glycosaminoglycan hyaluronan is found in pancreatic cancer. The role of hyaluronan synthases 2 and 3 (HAS2, 3) was investigated in pancreatic cancer growth and the tumor microenvironment. Overexpression of HAS3 increased hyaluronan synthesis in BxPC-3 pancreatic cancer cells. In vivo, overexpression of HAS3 led to faster growing xenograft tumors with abundant extracellular hyaluronan accumulation. Treatment with pegylated human recombinant hyaluronidase (PEGPH20) removed extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 60 publications
(137 reference statements)
4
87
0
2
Order By: Relevance
“…[15][16][17] Increased HA also prevents chemotherapeutic agents and monoclonal antibodies from reaching their sites of action. 8,9 HA accumulation in the TME is associated with accelerated tumor growth and is an independent, negative predictor of survival.…”
Section: The Tumor Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] Increased HA also prevents chemotherapeutic agents and monoclonal antibodies from reaching their sites of action. 8,9 HA accumulation in the TME is associated with accelerated tumor growth and is an independent, negative predictor of survival.…”
Section: The Tumor Microenvironmentmentioning
confidence: 99%
“…7 Within the TME, hyaluronan (HA) is a naturally occurring linear polysaccharide, and a major component of the tumor stroma in many solid tumors, including PDA. 8 In animal models, accumulation of HA increases tumor interstitial fluid pressure (IFP), which in turn compresses blood vessels and compromises blood flow. [9][10][11][12] This process leads to hypoxia in the tumor, which is a contributory factor in metastasis.…”
Section: The Tumor Microenvironmentmentioning
confidence: 99%
“…Has2 has been identified in vitro as significantly overexpressed in fibroblast coculture experiments with PDAC cells 39 and has been associated with significantly increased hyaluronic acid secretion. 40,41 Hyaluronic acid has been identified as a critical factor in the pancreatic tumor microenvironment that increases interstitial fluid pressure, collapsing potential vascular access to tumors. 10 PDAC xenografts utilizing over-expression of Has2 demonstrated increased tumor growth, loss of membranous E-cadherin and increased accumulation of cytoplasmic β-catenin.…”
Section: Etv1 Mediated Stromal Expansion Is Associated With Hyaluronimentioning
confidence: 99%
“…10 PDAC xenografts utilizing over-expression of Has2 demonstrated increased tumor growth, loss of membranous E-cadherin and increased accumulation of cytoplasmic β-catenin. 41 Indeed, Has2 has been associated with poorer survival in human PDAC. 42 We found Etv1 overexpression was associated with Has2 increase by 4 fold ( Figure 5A).…”
Section: Etv1 Mediated Stromal Expansion Is Associated With Hyaluronimentioning
confidence: 99%
“…In our previous study, we demonstrated overexpression and prognostic relevance of HA and its regulators in PDAC [17]. Recently, forced production and accumulation of extracellular HA by hyaluronan synthase (HAS) 3 overexpression have been shown to promote growth of PDAC tumor in mice [18]. These findings suggest the importance of HA in the progression of PDAC; however, only a few studies addressed its effects on the aggressive tumor phenotype, especially cell migration, in PDAC.…”
Section: Introductionmentioning
confidence: 99%